Autism Spectrum Disorders-A Review on The Preventive Aspects - Smitabh Barik; Lipilekha Patnaik; Sumitra Pattanaik (Medsci Publications, 2023)
Autism Spectrum disorder (ASD) is a neurodevelopmental disorder presenting with defects in social communication skills and repetitive sensory motor behaviour. There has been increasing concern regarding this disorder due to its increase in incidence and prevalence in recent years. Since it stays for lifelong and has no specific pharmacological treatment, many studies are being conducted to find ways of preventing this disorder. Better understanding of the causative factors will lead to better development of prevention strategies. This review aims at highlighting the methods of prevention of ASD which are mostly focussed on the environmental factors causing ASD as well as the ongoing researches on development of drugs and genetic modification using animal models. Some studies have shown preventive effects of factors such as nutrition supplements such as Vitamin D and folate, breastfeeding and avoiding exposure to harmful chemicals and drugs. The aim is to prevent the occurrence of the disorder and preventing the severity of symptoms wherever possible. Still more studies are needed to establish the exact association between the possible causative factors and ASD so that clinical trials can be done to establish the preventive effects in future.